The Marxist Feminism of Heleieth Saffioti - Gonçalves, Renata (Pontifícia Universidade Católica de São Paulo, 2011)
Paddling against the current of academic thinking of the 1960s in Brazil, Heleieth Saffioti was the first to review women’s conditions from a class perspective against the majority of Marxist studies that still defended the idea that capital was blind to sex differences. Her research highlights the entanglement that allows the capitalist mode of production to appropriate and reproduce the inequalities between the sexes.